2021
DOI: 10.1021/acs.jafc.1c05770
|View full text |Cite
|
Sign up to set email alerts
|

Wild Strawberry-like Flavor Produced by the Fungus Wolfiporia cocos─Identification of Character Impact Compounds by Aroma Dilution Analysis after Dynamic Headspace Extraction

Abstract: Brown-rot fungi are particularly suitable for the sustainable and cost-efficient biotechnological production of natural flavors. In this study, Wolfiporia cocos was employed for the fermentation of European black currant pomace supplemented with aspartate in surface cultures to produce a flavor reminiscent of wild strawberries. Aroma dilution analysis (ADA) by means of dynamic headspace extraction was developed as a suitable technique for solid samples. The character impact compounds were quantified by stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…These six compounds were followed by a group of 16 substances with the FD factor 4. This group included monoterpene hydrocarbons (e.g., β-pinene (5) and myrcene (6)), oxygenated monoterpenes (e.g., linalool (14), α-terpineol (16), nerol (18), and geranial (21)), monoterpenoid esters (e.g., neryl acetate (25) and geranyl acetate (26)), aliphatic aldehydes (e.g., decanal (17) and dodecanal (27)), a sesquiterpene (β-bisabolene (34)), an oxidized sesquiterpene (caryophyllene oxide (38)) and substituted coumarins and furocoumarins. This group of diverse compound classes hence showed a diverse spectrum of component specific odor descriptions.…”
Section: Screening For Potent Odorants In Citrus Latifolia Peelmentioning
confidence: 99%
“…These six compounds were followed by a group of 16 substances with the FD factor 4. This group included monoterpene hydrocarbons (e.g., β-pinene (5) and myrcene (6)), oxygenated monoterpenes (e.g., linalool (14), α-terpineol (16), nerol (18), and geranial (21)), monoterpenoid esters (e.g., neryl acetate (25) and geranyl acetate (26)), aliphatic aldehydes (e.g., decanal (17) and dodecanal (27)), a sesquiterpene (β-bisabolene (34)), an oxidized sesquiterpene (caryophyllene oxide (38)) and substituted coumarins and furocoumarins. This group of diverse compound classes hence showed a diverse spectrum of component specific odor descriptions.…”
Section: Screening For Potent Odorants In Citrus Latifolia Peelmentioning
confidence: 99%
“…W. cocos has been used to ferment several substrates in the past, and some of the odor-active compounds detected in this study have also been reported previously. Sommer et al (2021) fermented black currant pomace with W. cocos in solid-state fermentation. Supplementation of the solid-state cultures with sodium aspartate led to a wild-strawberry like odor.…”
Section: Aroma Compoundsmentioning
confidence: 99%
“…It is an edible medicinal mushroom, which is also known in China as Fu Ling or Indian Bread (Wang et al 2013). Highly fragrant compounds like linalool, methyl anthranilate, phenyl ethanol, benzaldehyde, methyl phenylacetate, and geraniol have been detected in several studies (Rigling et al 2021a;Sommer et al 2021;Wu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, natural flavors biosynthesized by basidiomycetes offer an alternative to those extracted from natural plant sources [2], flavors biosynthesized by basidiomycetes offer an alternative to those extracted from natural plant sources [2], since the odor spectra produced by basidiomycetes is most like that of plants [1,3]. Basidiomycetes, as the highest developed class of fungi, have shown their impressive capability to produce numerous natural flavors from a series of different plantbased substrates in the last years [1,[4][5][6][7]. Their unique and complex sets of extracellular enzymes [8,9] allow basidiomycetes to adapt well to not only different plant biopolymers but also simple nutrients such as sugars or amino acids to synthesize flavorings de novo [1,2].…”
Section: Introductionmentioning
confidence: 99%